FAST FASHION: ECONOMICALLY SOUND BUT A DISASTER FOR ENVIRONMENT. - Kaur, Navjot; Singh, Varinnder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fashion trends come and go; meanwhile, a society’s values are established and evolving according to its beliefs and culture. Fashion is not an ambitious projected image interpreted as good old value to fulfil some function or agenda but rather an evocative and refreshing concept worthy enough to be portrayed for society’s appreciation which makes us even more instinctive. Fashion, in and of itself, is a reflection of social, economic, political, and cultural developments. It represents modernism and the spirit of the times. The product is no longer the centre of attention: it is the brand that does. Fast fashion is a word used to characterise today’s instantly available, low-cost fashion. The term "fast" refers to how quickly merchants can transport designs from the runway to stores to keep up with the ongoing desire for more and new styles. While fair trade companies can attempt to compete with fast fashion retailers, markets for fair trade and eco-friendly textile manufacturing remain small and ethically and environmentally sound supply chains are difficult and expensive to audit. High-income countries can promote occupational safety and environmental health through trade policies and regulations. But in reality, there are no legally binding environmental standards enacted through government regulation. Left unregulated, the industry will be responsible for more than 25% of the world’s global carbon budget by 2050. Reducing emissions, water and energy use, increasing collection and reuse: MEPs want ambitious science-based targets to reduce greenhouse gas emissions in the entire lifecycle of the textiles sector. Fast fashion is big business, and while the environmental costs are rising, experts say there is another way: a circular economy for textiles. Environmental justice is defined by the United States Environmental Protection Agency, as the “fair treatment and meaningful involvement of all people regardless of race, colour national origin, or income, concerning the development, implementation, and enforcement of environmental laws, regulations and policies. The term ‘fast fashion’ has become more prominent in conversations surrounding fashion, sustainability, and environmental consciousness. In this article, the researcher wishes to discuss the impact that expanding fashion has on the environment and offer some clever solutions to assist it decline.